2018
DOI: 10.18203/issn.2455-4510.intjresorthop20183682
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of 50 cases of patella fractures treated with different modalities

Abstract: <p class="abstract"><strong>Background:</strong> Fractures of patella account for 1% of all skeletal injuries. There is no universal accepted treatment for patellar fractures. After a fracture of the patella, the best results are obtained by accurate reduction and stable internal fixation. Partial or total patellectomy is generally indicated when the patella is so severely comminuted that an accurate reduction and reconstruction of the retropatellar joint surface cannot be achieved.</p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Excellent results were significantly higher in our study as compared to 17% good results and 11% fair results. This was significantly higher in comparison to a similar study conducted by Rajesh V Chawda, Parag Tank et al which had 25% excellent results, 46.87 percent good results and 15 percent patients with poor results[9]. Similar related study was reported by Sharma et al[10].…”
supporting
confidence: 51%
“…Excellent results were significantly higher in our study as compared to 17% good results and 11% fair results. This was significantly higher in comparison to a similar study conducted by Rajesh V Chawda, Parag Tank et al which had 25% excellent results, 46.87 percent good results and 15 percent patients with poor results[9]. Similar related study was reported by Sharma et al[10].…”
supporting
confidence: 51%